2021
DOI: 10.22541/au.161963333.37636342/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coalescence times, life history traits and conservation concerns: an example from four coastal shark species from the Indo-Pacific

Abstract: Dispersal abilities play a crucial role in shaping the extent of population genetic structure, with more mobile species being panmictic over large geographic ranges and less mobile ones organized in meta-populations exchanging migrants to different degrees. In turn, population structure directly influences the coalescence pattern of the sampled lineages, but the consequences on the estimated variation of the effective population size (Ne) over time obtained by means of unstructured demographic models remain po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 34 publications
5
14
0
Order By: Relevance
“…All three SFS displayed an excess of singletons in comparison to the one inferred by ANGSD (Figure S6b), clearly determining not only a stronger ancestral expansion but also the absence of the recent bottleneck when fed to the stairwayplot algorithm (Figure S6a). We note that by using the generation time and mutation rate of Walsh et al (2022) (a mutation rate only relevant to exon capture data (Maisano Delser et al, 2016) thus lower than the one estimated for RAD-seq data (Lesturgie et al, 2022)), the Ne variation reconstructed by the stairwayplot applied to our PyRAD assembly was highly similar to the results they obtained in their Chesterfield sampling sites (compare our Figure 6b with their Figure 3). Consequently, we highlight that the SFS reported by (Walsh et al, 2022) is biased toward an excess of low frequency variants, skewing their inferred genetic diversity and the subsequent demographic modelling.…”
Section: Range Expansionsupporting
confidence: 74%
See 4 more Smart Citations
“…All three SFS displayed an excess of singletons in comparison to the one inferred by ANGSD (Figure S6b), clearly determining not only a stronger ancestral expansion but also the absence of the recent bottleneck when fed to the stairwayplot algorithm (Figure S6a). We note that by using the generation time and mutation rate of Walsh et al (2022) (a mutation rate only relevant to exon capture data (Maisano Delser et al, 2016) thus lower than the one estimated for RAD-seq data (Lesturgie et al, 2022)), the Ne variation reconstructed by the stairwayplot applied to our PyRAD assembly was highly similar to the results they obtained in their Chesterfield sampling sites (compare our Figure 6b with their Figure 3). Consequently, we highlight that the SFS reported by (Walsh et al, 2022) is biased toward an excess of low frequency variants, skewing their inferred genetic diversity and the subsequent demographic modelling.…”
Section: Range Expansionsupporting
confidence: 74%
“…Second, the historical demography inferences performed in each sampled deme showed that the pattern of genetic variability was most likely the outcome of a non-equilibrium meta-population structured according to a stepping stone migration matrix (Table 2). In this context, both the colonization times of the meta-population estimated by the ABC (Figure S2) and the expansion times retrieved by the stairwayplot (Figure 4) harbour the signature of the RE process (Lesturgie et al, 2022): the oldest times are expected to be close to the centre of origin of the RE, while the more recent ones are likely associated to the edge of the colonization wave(s). While the large variance in Tcol estimated by ABC does not allow for an accurate interpretation of the temporal dynamics of colonisation through the Indo-Pacific, the expansion times highlighted by the stairwayplot are consistent with the RE scenario.…”
Section: Range Expansionmentioning
confidence: 94%
See 3 more Smart Citations